2021
DOI: 10.1007/s12325-021-01832-5
|View full text |Cite
|
Sign up to set email alerts
|

How to Tackle the Diagnosis and Treatment in the Diverse Scenarios of Extrapulmonary Sarcoidosis

Abstract: Extrapulmonary sarcoidosis occurs in 30-50% of cases of sarcoidosis, most often in association with pulmonary involvement, and virtually any organ can be involved. Its incidence depends according to the organs considered, clinical phenotype, and history of sarcoidosis, but also on epidemiological factors like age, sex, geographic ancestry, and socio-professional factors. The presentation, symptomatology, organ dysfunction, severity, and lethal risk vary from and to patient even at the level of the same organ. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 103 publications
(152 reference statements)
0
13
0
2
Order By: Relevance
“…Vahdani’s thirty-year retrospective study found only 61 patients affected by orbitopathy in this long period of time. Systemic involvement was found in 23 (62%) patients initially presenting with orbital disease [ 242 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vahdani’s thirty-year retrospective study found only 61 patients affected by orbitopathy in this long period of time. Systemic involvement was found in 23 (62%) patients initially presenting with orbital disease [ 242 ].…”
Section: Discussionmentioning
confidence: 99%
“…Benign disorders as differential diagnosis of diffuse lymphadenopathy include (1) infectious etiologies, such as histoplasmosis and HIV; (2) inframammary disease due to granulomatous and autoimmune diseases; and (3) benign lymphoproliferative disease, such as Castleman’s disease [ 20 ]. The interpretation of this patient’s PET scan was impacted by the undiagnosed systemic sarcoidosis, a disease that often demonstrates avidity on PET [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcoidosis is a multisystemic, non-caseous, benign granulomatous disease of unknown etiology with the incidence estimated to be 50 to 150 per 100,000 population [ 22 ]. The diagnosis of sarcoidosis is based on the histopathological finding demonstrating noncaseating granulomas [ 21 ]. Sarcoidosis can affect any organ, including the liver and spleen.…”
Section: Discussionmentioning
confidence: 99%
“…Descrita en 1869 por Carl William Boeck cuando les dio el nombre a múltiples lesiones sarcoidales benignas en las regiones extensoras de los miembros superiores de un paciente de 36 años. Además, existen variación no solo en la prevalencia de la enfermedad, si no en su forma de presentación de acuerdo con la raza, siendo más frecuentes las formas crónicas y el compromiso ocular en la población afrodescendiente y las formas asintomáticas en la población blanca, en el caso que se presenta importante mencionar que es afrodescendiente, con una evolución crónica de las lesiones der-matológicas por la que consultó [10][11][12][13] .…”
Section: Discussionunclassified